Selling Spectacular Urban Life: Urban Space and Lifestyle in the Promotion Media of Apartment in Yogyakarta - Ratna Noviani; Elok Santi Jesica (Journal of Urban Society's Arts, 2021)
This article discusses how urban life is represented through the Barsa City, Uttara the Icon, and The Palace apartment advertisements and promotional videos. Applying Guy Debord's idea of spectacle to examine how urban life is transformed into visualization and commodification, also George Ritzer’s idea of re-enchantment of the disenchanted world and the new means of consumption. This article is aimed to analyze the position of apartments in the urban space of Yogyakarta that is discursively constructed through apartment promotional media. The conclusion of this research shows that apartments are functionalized to create the spectacle of the city. Urban space and life are aestheticized and spectacularized, in which apartments are displayed as part of dramatic and extravagant urban arts. Presented as one-stop-serving buildings, the apartments also promote the fusion of living space, urban style experience, and consumption which lead to the difficulty in distinguishing spatial boundaries. The advertisements and promotional videos of the apartment in Yogyakarta also promote temporal paradox. On the one hand, it promotes time compression and speed, meanwhile, on the other hand it promotes prolonged and extended time to foster consumption in the urban space.